Neutrality of Technical Progress - Resek, Robert W. (The Review of Economics and Statistics, 1963)
Technical Change R ECENT studies have attempted to derive the relative proportions of total increase in output that are caused by growth in capital stock and by technical advance. These studies seem to have turned attention away from capital formation as a source of growth to technical change as the only important factor. Each of these papers has assumed, explicitly or implicitly, that the technical change takes place in a neutral fashion. The present paper examines this assumption and finds it to be questionable. In this light, new estimates of the importance of capital formation are found. The first important recent paper attempting to measure technical change was presented by Robert Solow.' He concluded that technical change is neutral on the average, that there was little basis of choice with his data among five possible production functions, and that about 87?2 per cent of the increase in gross output per man hour is attributable to technical change, and I2/2 per cent to increased use of capital. Other authors with various techniques have studied the relative importance of capital and of technical progress. Niitamo made a regression model of production in Finland and found most of the increase was attributable to the passage of time and to education, and little was attributable to capital formation.2 He concluded that emphasis should be taken away from capital as an aid to economic growth and placed instead on these other factors which he lumped together as the human factor. Massell made a study with improved data that used the same methods as Solow but which annlied only to the manufacturing sector.3 His results again gave the greatest importance to technical change. He said,